Analisis Perbandingan Kinerja Keuangan Sebelum dan Selama Pandemi Covid-19 pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Pramesty, Ega Notria Anggun; Dwiarti, Rina (Peneliti.net, 2023)
The Covid-19 virus is a virus that was discovered in December 2019 in the Chinese city of Wuhan. Covid-19 not only has an impact on the health sector but also has an impact on the global economy. As part of an economic system, the food and beverage sector is also affected. The purpose of this study is to determine differences in the financial performance of food dan beverage companies listed on the IDX by comparing before and during the Covid-19 pandemic. Financial performance in food and beverage companies consists of Total Assets Turn Over Ratio (TATO), Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA). The population in this study totaled 44 food and beverage companies listed on the IDX during the 2019-2021 period, but in this study a sample of 25 companies was taken because there were 8 companies that did not issue annual financial reports. The type of data used in this study secondary data obtained from annual reports and financial reports published through the Indonesian Stock Exchange website and the website of each company. The result showed that there was no difference in the ratios of TATO, CR, DER, ROA before and during the Covid-19 pandemic.